2016
DOI: 10.1128/aac.02071-15
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin Binding Protein 1 Is Important in the Compensatory Response of Staphylococcus aureus to Daptomycin-Induced Membrane Damage and Is a Potential Target for β-Lactam–Daptomycin Synergy

Abstract: fThe activity of daptomycin (DAP) against methicillin-resistant Staphylococcus aureus (MRSA) is enhanced in the presence of ␤-lactam antibiotics. This effect is more pronounced with ␤-lactam antibiotics that exhibit avid binding to penicillin binding protein 1 (PBP1). Here, we present evidence that PBP1 has a significant role in responding to DAP-induced stress on the cell. Expression of the pbpA transcript, encoding PBP1, was specifically induced by DAP exposure whereas expression of pbpB, pbpC, and pbpD, enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 35 publications
1
34
1
Order By: Relevance
“…Support for this hypothesis comes from recent data, which demonstrate that fosfomycin appears to reduce PBP1 expression in S. aureus (10). PBP1 expression is increased with daptomycin exposure and is believed to be important in the bacterial compensatory response in response to peptide-induced injury (46). Thus, either pharmacologic antagonism of PBP1, as seen with beta-lactam antibiotics, or compromising expression of key compensatory proteins like PBP1 by fosfomycin may be a foundation for increasing daptomycin-mediate bacterial killing efficiency.…”
Section: Discussionmentioning
confidence: 98%
“…Support for this hypothesis comes from recent data, which demonstrate that fosfomycin appears to reduce PBP1 expression in S. aureus (10). PBP1 expression is increased with daptomycin exposure and is believed to be important in the bacterial compensatory response in response to peptide-induced injury (46). Thus, either pharmacologic antagonism of PBP1, as seen with beta-lactam antibiotics, or compromising expression of key compensatory proteins like PBP1 by fosfomycin may be a foundation for increasing daptomycin-mediate bacterial killing efficiency.…”
Section: Discussionmentioning
confidence: 98%
“…Previously, an affinity for certain penicillin-binding proteins (PBPs) has been demonstrated to predict an enhancement of DAP activity, with activity against PBP 1 in staphylococci and PBP 5 in enterococci being important (23,40,(42)(43)(44). The most recent data available suggest that the synergy achieved with the carbapenems ertapenem and imipenem, which are selective for PBP 1, in combination with DAP is superior to that achieved when DAP is used in combination with other beta-lactams, including NAF, which possesses nonselective activity against PBPs (44).…”
Section: Discussionmentioning
confidence: 99%
“…We previously observed that DAP-mediated sensitization to ␤-lactams occurred with those ␤-lactams that preferentially target PBP 1 or PBP 2, including NAF (PBP 1, PBP 2), IPM (PBP 1), and CTX (PBP 2), whereas no changes were observed with ␤-lactams targeting PBP 4, such as cefoxitin (FOX), or PBP 3, such as cefaclor (CEC) (8,21,22). Similar effects were observed in other in vitro-selected DAP r mutants obtained from DAP s CB1631 (DAP r CB1631 mutants) and CB5011 (DAP r CB5011 mutants) (8).…”
mentioning
confidence: 99%